Association between age and serum ferritin level with bone age deficit in children with thalassemia major - Sri Hastuti Andayani; Nanan Sekarwana; Ryadi Fadil (Paediatrica Indonesiana, 2008)
Background Multiple blood transfusions in thalassemia patients lead to iron overload in bone tissue. Iron overload can be determined by serum ferritin measurement. Several studies have evaluated association between serum ferritin level and growth, but without bone age examination. Objective To determine the association between age and serum ferritin level with bone age in children with thalassemia major. Methods This study was conducted at Hasan Sadikin Hospital Bandung during March-May 2007. We performed physical examination, serum feritin measurement, and bone age examination. Data were analyzed with x 2 to determine association between variables. The association between age and serum ferritin level with bone age deficit was analyzed with regression logistic model. Results Subjects consisted of 49 patients with thalassemia major. All subjects had bone age deficit. Most boys were in age group of >10 years and had bone age difference >36 months, while most girls were <10 years and had bone age difference <36 months. Subjects with bone age difference <36 months mostly had serum ferritin level <5,000 ng/dL, while most subjects with bone age difference >36 months had serum ferritin level =5,000 ng/dL. This was statistically significant (x 2 =4.573, P=0.032). There was association between age and bone age deficit (OR=13.461, 95% CI 3.199;56.640), but not with serum ferritin level (OR= 2.199, 95% CI 0.532;9.095). Conclusion In thalassemic children, bone age deficit is associated with age, but not with serum feritin level.